Application of Virtual Gallery Walk with Spatial.Io in An Effort to Increase Students’ Learning Motivation in Social Studies - Choiroh, Dista Ayu Umdatul; Kurniawan, Bayu; Rahayu, Linda Zulkifa; Wati, Arista; Sari, Erna (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The aim of this study is to enhance students’ motivation in learning Social Studies (IPS) through the implementation of a virtual gallery walk learning model using Spatial.io. Spatial.io was selected because it offers an immersive 3D learning environment that supports interactive learning experiences. This research adopts a design thinking approach, consisting of five stages: empathize, define, ideate, prototype, and test. The subjects of the study were 8th-grade students from class 8A at SMP Laboratorium UM Malang. The developed product demonstrated that the application of a virtual gallery walk using Spatial.io effectively increased students’ learning motivation, as evidenced by higher levels of active participation, enthusiasm, and positive feedback throughout the learning process.